Synthesis and self-assembly of amphiphilic homoglycopolypeptide - Dhaware, Vinita; Shaikh, Ashif Y.; Kar, Mrityunjoy; Hotha, Srinivas; Sen Gupta, Sayam (Langmuir, 2013)
The synthesis of the amphiphilic homoglycopolypeptide was carried out by a combination of NCA polymerization and click chemistry to yield a well-defined Polypeptide having an amphiphilic carbohydrate on its side chain. The amphiphilicity of the carbohydrate was achieved by incorporation of an alkyl chain, at the C-6 position of the carbohydrate thus also rendering the homoglycopolypeptide amphiphilic. The homoglycopolypeptide formed multimicellar aggregates in water above a critical concentration of 0.9 mu M due to phase separation. The multimicellar aggregates were characterized by DLS, TEM, and AFM. It is proposed that hydrophobic interactions of the aliphatic chains at the 6-position of the sugar moieties drives the assembly of these rod-like homoglycopolypeptide into large;spherical aggregates. These multimicellar aggregates encapsulate both hydrophilic as well as hydrophobic dye as was confirmed by confocal microscopy. finally, amphiphilic random polypeptides containing 10% and 20% alpha-D-mannose in addition to glucose containing a, hydrophobic alkyl chain at its 6 position were synthesized by our methodology, and these polymers Were also found to assemble into spherical nanostructures. The spherical assemblies Of amphiphilic random glycopolypeptides containing 10% and 20% mannose were found to be surface bioactive and were found, to interact with the lectin Con-A.